Commercial banks as a mechanism against financing terrorism - Dimitrova, T. (Економічний вісник Донбасу, 2017)
In the process of globalization, the need to block financial flows to terrorist organizations is becoming more and more tangible. The fight against terrorist financing is becoming a national and supranational priority, and credit institutions are among the main mechanisms for committing such crimes, and are therefore covered by numerous regulations and institutions concerning their role in controlling and preventing them. The purpose of this study is to outline the commercial banks' place in terrorist financing processes by presenting their inherent characteristics within the scope of the Special Act on Measures Against Financing of Terrorism.